2006
DOI: 10.1002/app.24164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of temperature and crystallinity profiles of wood sawdust/polypropylene composites during cooling

Abstract: The temperature profiles of wood sawdust/ polypropylene (PP) composite melts during cooling were experimentally investigated with a cooling jacket apparatus connected to the end of an injection-molding machine. Real-time melting temperature was measured with an unsheathed thermocouple array coupled with a high-speed data-acquisition unit. The crystallinity level of the solidified composites was evaluated with an X-ray diffractometer. Before the crystallization temperature (T c ) was reached, the cooling rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Again, this implies that PLA could not be recrystallized under the above cooling rate. 21 The above notion was also supported by considering the results from isothermal DSC thermograms of the composites, which was described in the subsequent section. In this regard, the effects of annealing conditions on thermomechanical properties of PLA compounds deserve a consideration.…”
Section: Resultsmentioning
confidence: 62%
“…Again, this implies that PLA could not be recrystallized under the above cooling rate. 21 The above notion was also supported by considering the results from isothermal DSC thermograms of the composites, which was described in the subsequent section. In this regard, the effects of annealing conditions on thermomechanical properties of PLA compounds deserve a consideration.…”
Section: Resultsmentioning
confidence: 62%
“…These results that the wood particles acted as a nucleating agent in the LDPE matrix, although the melting temperature of LDPE did not obviously change. The increase in the crystallinity level could be supported by the work of Amash and Zugenmaier [37], Kositchaiyong and Sombatsompop [38], and Quan et al [39], who suggested that cellulose fibers may act as a heterogeneous nucleating agent and nucleate crystallization along the interface. These nuclei would hinder the lateral extension and force growth in one direction, namely perpendicularly to the fiber surfaces, and result in a columnar crystalline layer, known as trans‐crystallinity, leading to a higher crystallinity level.…”
Section: Resultsmentioning
confidence: 88%
“…Another study conducted by Sombatsompop et al [9] reported that the addition of poly(propylene) powder generated higher Tc. According to their interpretation, the powder in a poly(propylene) timber was effective to form nucleation of the crystallization at higher temperatures.…”
Section: Effect Of Pp-g-ma On Dsc Of Compositesmentioning
confidence: 97%